ON THE INHOMOGENEITY OF VOLCANIC GLASS AND THE ORIGIN OF AMYGDULES IN BASALTS - Lyashkevich Z.M.; Marushkin A.I.; Tkach V.N. (My University, 1989)
In the course of a microprobe study of volcanic glass, we obtained new data suggesting the possibility of a different mode of formation of amygdules. We studied samples of oceanic volcanic glass in the form of incrustations 2-3 cm thick that evidently come from the quenched zone of basalt flows. Judging by the bulk chemical composition of the glass samples, they correspond to melanocratic alkali-poor basalts. The hypersthene-diopside composition of the normative mafic minerals, the admixture of quartz and the low value of the agpaite coefficient indicate that these basalts are of the alkali-earth tholeiitic type. The Fe2O3/FeO ratio is less than unity, evidently indicating oxidizing processes in the quenched zone. The magmatic formation of amydgules proposed here may be one possible version of the formation of amygdaloidal structures in the surface zones of basalt flows.